2012
DOI: 10.1080/00028487.2012.654889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Catchable‐Sized Hatchery Rainbow Trout on Wild Rainbow Trout Abundance, Survival, Growth, and Recruitment

Abstract: The Idaho Department of Fish and Game has proactively dealt with the potential adverse genetic effects of stocking catchable-sized hatchery trout in waters that support native salmonids by adopting a policy in 2001 whereby only sterile rainbow trout Oncorhynchus mykiss are stocked in flowing waters; however, concerns regarding the competitive effects of introducing hatchery trout into streams and rivers supporting wild trout have not been addressed. We stocked fish in the middle 3 years of a 5-year study to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
(89 reference statements)
1
18
0
Order By: Relevance
“…, Meyer et al. ). Our model supports the trend seen in some countries to stock increasingly larger fish including catchable fish in stock‐enhancement efforts (Halverson ), which is likely a response to fry and small fingerlings rarely producing sustained outcomes for ecological reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Meyer et al. ). Our model supports the trend seen in some countries to stock increasingly larger fish including catchable fish in stock‐enhancement efforts (Halverson ), which is likely a response to fry and small fingerlings rarely producing sustained outcomes for ecological reasons.…”
Section: Discussionmentioning
confidence: 99%
“…, Meyer et al. ). The recommendation to stock a nonnative species such as carp also assumes that one is not concerned with the possible negative ecological consequences of high carp biomasses (e.g., water quality impacts, habitat degradation, competition with other species, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Most fishery resource managers are charged with the dual, often conflicting responsibility of providing and enhancing angling opportunities for the public while simultaneously protecting native organisms (Meyer et al 2012). This dual mandate suggests that stocking of non-native trout is likely to continue in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies examining the ecological impacts of stocked or introduced trout in streams and lakes at varying spatial scales have ranged from finding little or no effect (Allan 1982;Zimmerman & Vondracek 2007;Hanisch et al 2012;Meyer et al 2012) to observing large impacts on invertebrate abundances, biomass, or density (Flecker and Townsend 1994;Huryn 1998;Nakano 1999;Baxter et al 2004). For example, Baxter et al (2004) showed that stocked rainbow trout CONTACT Alexander V. Alexiades ava29@cornell.edu monopolized terrestrial invertebrates and caused native fish to shift their diet to insect grazers, thereby increasing algal biomass.…”
Section: Introductionmentioning
confidence: 99%
“…To assess how programs balance providing harvest options of non-local animals through intentional releases, such as putand-take fisheries (Johnson et al 1995, Meyer et al 2012b, big game hunting preserves (Adams et al 2016), and upland bird introductions (Blanco-Aguiar et al 2008), with conservation of endemic populations, quantification of the proportion of Fig. Post-release fate may affect native conspecifics, similar species within the same guild or assemblage (i.e., other cold-water fishes), community dynamics via food web effects, or energy and nutrient flows within the recipient ecosystem.…”
Section: Harvest and Non-local Translocationmentioning
confidence: 99%